Energy-efficient three-phase bidirectional converter for grid-connected storage applications. (1st November 2016) - Colmenar-Santos, Antonio; Linares-Mena, Ana-Rosa; Velázquez, Jesús Fernández; Borge-Diez, David
Graphical abstract: Highlights: Storage control system developed based on AC DC three phase bidirectional converter. Bidirectional AC DC converter for storage integration into distribution grids. Efficiencies over 98% for values over 30% of the bidirectional converter rated power. Sensitivity analysis of the parameters set by the transmission system operator. Low-cost option for control and integration of new grid-connected storage systems. Abstract: Grid connected energy storage systems are expected to play an essential role in the development of Smart Grids, providing, among other benefits, ancillary services to power grids. It is therefore crucial to design and develop control and conversion systems that represent the key instrument where intelligence for decision-making is applied, in order to validate and ensure its optimal operation as part and parcel of the electrical system. The present research describes the design and development of a battery energy storage system based on an AC-DC three-phase bidirectional converter capable of operating either in charge mode to store electrical energy, or in discharge mode to supply load demands. The design is modelled with MATLAB® Simulink® environment in order to evaluate the performance during load variations. Moreover, the assessment is complemented by a global sensitivity analysis for variations in the operating parameters set by the transmission system operator. The effectiveness of the simulation is confirmed by implementing the system and carrying out grid connection tests, obtaining efficiencies over 98% for values over the 30% of the bidirectional converter rated power.